CODE MIXING USED BY THE PRESENTER ON VISI FM - Pinta Omasuli Panjaitan; Yunita Agnes Sianipar (State University of Medan, 2014)
ABSTRACT This study deals with code-mixing used by presenters on VISI FM. The objectives of this study are to : (1) find out the forms ofcode-mixing, that are used by VISI FM’s presenters. (2) find out the form of code- mixing that is dominantly used by VISI FM’s presenter. This research applied descriptive quantitative method.The object of this study is presenter of VISI FM namely Deris and Lia. The tape recorder is used for collecting the data where the utterence of presenters were recorded while presenting that program.After collecting the data, the writer found that forms of code mixing occured in the presenters’s utterances are code mixing in forms words, phrases, and sentences. Code mixing in form of word is dominantly used by male presenters namely Deris, where the percentage of the occurrence of code mixing in his utterances are 255 code mixing, where there are 29 code mixing in form of sentences, 92 code mixing in form of phrases, and 133 code mixing in form of words and code mixing in form of sentence is dominantly used by female presenter namely Lia where the percentage of the occurrence of code mixing in her utterances are 184 code mixing occured where there are 82 code mixing in form of sentences, 44 code mixing in form of phrases, and 58 code mixing in form of words. Keyword : Code Mixing